PROBLEM-SOLVING ORIENTED GROUP APPROACH FOR REDUCING CONCERNS ASSOCIATED WITH TRANSITION TO TERTIARY INSTITUTIONS AMONG SENIOR SECONDARY SCHOOL STUDENTS IN ILORIN METROPOLIS, KWARA STATE, NIGERIA - Yahaya Lasiele Alabi; Salman Adisa; Aminu Popoola (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2023)
The study adopted a quasi-experimental design of pre-test, post-test and control group involving (two treatment groups and one control group), with problem-solving oriented group counselling approach which involves social skills training and modelling counselling technique adopted for reducing various concerns associated with transition to tertiary institutions among secondary school students in Ilorin metropolis, Kwara State, Nigeria. Paired sample t-test and Analysis of Co-Variance (ANCOVA) were used to test the five null hypotheses formulated for the study. All the hypotheses were tested at .05 level of significance. The findings of the study revealed that a problem-solving oriented group approach of social skills training, t = 9.45; p .05) and modelling intervention, 13.32; p .05) were effective in reducing concerns associated with transition to tertiary institutions among the secondary school students in Ilorin metropolis. It was also found that differential effect existed between the two counselling techniques used in the study (t = 2.84; p .05) and there was no gender difference in the participants post-test results of the two counselling groups (F = .663 and 1.227; p .05).